2020
DOI: 10.2147/ndt.s236034
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Parameters in Patients with Prader-Willi Syndrome and DiGeorge Syndrome with Respect to Psychopathological Manifestation</p>

Abstract: Purpose: The purpose of our study was to compare the metabolic parameters in two genetic syndromes with a proven high risk of developing psychiatric comorbidities. These comorbidities, especially mood and psychotic disorders, may be associated with a risk of obesity, type 2 diabetes and other components of metabolic syndrome regardless of antipsychotic treatment. Patients and Methods: Two groups of children diagnosed with Prader -Willi syndrome (PWS) (n = 20) and DiGeorge syndrome (DGS) (n = 18), aged 7-18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In a study of 207 adults with 22q11.2DS, 43.5% were obese, which was significantly higher than the general population (Voll et al, 2017). Krefft et al (2020) showed impaired insulin sensitivity was more common in Prader-Willi syndrome (PWS) and 22q11.2DS (without antipsychotic medication) compared to the general population. Furthermore, the risk of obesity doubled in those on psychotropics though not specifically antipsychotic medication (Voll et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 207 adults with 22q11.2DS, 43.5% were obese, which was significantly higher than the general population (Voll et al, 2017). Krefft et al (2020) showed impaired insulin sensitivity was more common in Prader-Willi syndrome (PWS) and 22q11.2DS (without antipsychotic medication) compared to the general population. Furthermore, the risk of obesity doubled in those on psychotropics though not specifically antipsychotic medication (Voll et al, 2017).…”
Section: Discussionmentioning
confidence: 99%